THE TRANSLATION OF IMAGINARY CONCEPTS AND WORLDS IN SCIENCE FICTION ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
Science fiction is a genre defined by its exploration of imaginary worlds, speculative technologies, and unconventional realities. Translating such texts presents unique challenges, as many concepts have no direct equivalents in the target language or culture. This paper examines the strategies used to translate imaginary concepts and fictional worlds in science fiction. It focuses on the role of creativity, cultural adaptation, and linguistic innovation in preserving both meaning and aesthetic effect. The study argues that successful translation requires not only linguistic accuracy but also the ability to reconstruct entire conceptual systems for the target audience.